2018
DOI: 10.1002/pola.29296
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous copolyesters based on bibenzoic acids and neopentyl glycol

Abstract: High Tg amorphous copolyester thermoplastics were synthesized by incorporating 4,4′‐bibenzoate (4,4′BB) and 3,4′‐bibenzoate moieties into the polyester backbone via melt polycondensation. The high levels of crystallinity typically associated with 4,4′BB containing polyesters were suppressed through copolymerization of ethylene glycol, 1,4‐cyclohexane dimethanol, and neopentyl glycol (NPG) diols. NPG was shown to be highly effective in suppressing crystallization and was used to produce amorphous compositions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Bibenzoate-based (BB) semi-aromatic polyesters possessing mechanical properties similar to BPA-PC, T g s greater than 100 °C, oxygen barrier properties greater than poly­(ethylene terephthalate) (PET), and potentially low manufacturing cost offer a novel polymer platform for improved thermoplastics. Enhanced mechanical, gas barrier, and thermal properties offer advantages in coating, food packaging, and high temperature electronic applications. These polyesters exhibit T g s approaching 120 °C, whereas BPA-PC T g is ∼145 °C, enabling BPA replacement in many high temperature applications.…”
Section: Introductionmentioning
confidence: 99%
“…Bibenzoate-based (BB) semi-aromatic polyesters possessing mechanical properties similar to BPA-PC, T g s greater than 100 °C, oxygen barrier properties greater than poly­(ethylene terephthalate) (PET), and potentially low manufacturing cost offer a novel polymer platform for improved thermoplastics. Enhanced mechanical, gas barrier, and thermal properties offer advantages in coating, food packaging, and high temperature electronic applications. These polyesters exhibit T g s approaching 120 °C, whereas BPA-PC T g is ∼145 °C, enabling BPA replacement in many high temperature applications.…”
Section: Introductionmentioning
confidence: 99%
“…Melt transesterification and polycondensation enabled the synthesis of the 3,3'BB‐based polymers utilizing well‐defined polymerization procedures, depicted in Scheme 1 12–15, 17, 31, 32 . In previous studies, the titanium isopropoxide catalyst chosen for this polymerization demonstrated catalytic activity towards transesterification 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Dimethyl 3,4′‐bibenzoate (3,4'BB), the kinked regioisomer of 4,4'BB, recently garnered interest after a number of studies emerged copolymerizing 4,4'BB and 3,4'BB with various diols. These studies demonstrated improvements to gas permeability and Young's modulus in the amorphous state upon increased incorporation of 3,4'BB 12–16 . This monomer imparted a higher amorphous polymer density as well as an increased entanglement density 13, 16 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several diacids/diesters such as purified terephthalic acid (PTA) and 2,5-dimethyl furanedicarboxylate (DMFD) were also investigated. Recently, new insights have been gained on bicyclic structures such as 3,4′-bibenzoate (3,4′BB) and 4,4′-bibenzoate , (4,4′BB), indole (IND), divanillic acid, and dimethyl [2,2′-bifuran]-5,5′-dicarboxylate. , …”
Section: Introductionmentioning
confidence: 99%